Total hip arthroplasty (THA) in a patient with subcapital femoral neck fracture and ipsilateral above-knee amputation: A case report - Francesco Maria Milella; Massimiliano Paolocci; Emanuele Persi; Riccardo Mezzoprete (Trauma Case Reports)
This case report describes the surgical and post-operative challenges encountered following a THA performed for a subcapital femoral neck fracture in a patient with an ipsilateral above-knee amputation.